Mushaf Imla’i dan Implikasinya dalam Pembacaan Al-Quran - Daud Ismail; Asyraf Hj Ab Rahman (Universiti Sains Islam Malaysia, 2024)
Imla’i Mushaf is one of the Quranic version written based on the standard Arabic writing. It is also known as Rasm Imla’i or Rasm Qiyasi. The structure of the Quranic rasm (orthography) and its dabt (conventional signs determining the proper pronunciation of Qur’an) in Imla’i Mushaf is different from the Uthmani Mushaf due to several factors such as the addition of the letters (ziyadah), exchanges of letters (badl) and some others. These differences to some extent led to some confusion and mistakes in the readings of the Quran. This article therefore will discuss some implication that arise as a result of using imla’i mushaf in reading the Quran and some consequences to Muslim communities as a whole. Using content analysis method, the study found that Imla’I Mushaf was not suitable to be used publicly as it may result to some confusion in terms of reading the Holy Quran.